2010
DOI: 10.1016/s0975-3575(10)80042-2
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Antimicrobial analysis of the crude extract, petroleum ether and chloroform fractions of Euphorbia heterophylla Linn Whole Plant

Abstract: Infectious diseases are main causes of morbidity and mortality in man, especially in developing countries. [1] The emergence of multidrug resistant organisms to known antibiotics leading to several deaths worldwide has led to the interest of scientists in exploring plants, herbal products and traditional medicine for the identification of safe and effective remedies to ailments of microbial origin. [2] Euphorbia heterophylla Linn belongs to the family Euphorbiaceae, a family represented by the trees, shrubs, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Ishir et al [21] reported "the presence of saponins in the methanolic stem extract of Amaranthus spinosus". "The presence of saponins and alkaloids have been reported to be responsible for various pharmacological properties with alkaloids exerting toxic effects against cells of foreign organism" [22].…”
Section: Resultsmentioning
confidence: 99%
“…Ishir et al [21] reported "the presence of saponins in the methanolic stem extract of Amaranthus spinosus". "The presence of saponins and alkaloids have been reported to be responsible for various pharmacological properties with alkaloids exerting toxic effects against cells of foreign organism" [22].…”
Section: Resultsmentioning
confidence: 99%
“…This study lists 127 Karen medicinal species used for treatments of infectious diseases, but only a few of them were used for many different types of infection and several were used only for a single infection type (Table 1). Although these species had low CI values, other studies have shown that some of them have antimicrobial activities, such as Acmella oleracea [42], Euphorbia heterophylla [43], Peperomia pellucida [44], and some other species listed in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…The milky latex is acrid and the toxicity is neither alkaloid nor glycoside but probably a resin which can prove fatal [12]. Despite the toxicity hazard of this plant, it has various medicinal properties which include its use in the treatment of gonorrhea, respiratory tract infection, malaria, eczema, asthma, and wart cure [13].…”
Section: Introductionmentioning
confidence: 99%